An integrated solar thermal and photovoltaic system - Hawlader, Mohammad Nurul Alam; Ihsan, Sany Izan; Joseph, Deepu; Hamid, N Munira; Wasil, Wira E A (2012)
For the conversion of solar irradiation directly to electricity, Photovoltaic (PV) cells play an excellent role. Absorption of radiation beyond wave length 0.35 – 0.82 µm leads to a rise in temperature and the performance is significantly reduced as a result of temperature rise. Many attempts have been made to maintain the operating temperature of the PV cells as low as possible using both water and air cooling system fitted at the back of the panel. In this project, extensive indoor and outdoor tests have been performed to develop an integrated system to filter component of solar irradiation contributing to a temperature rise of the PV panel. For indoor tests, a Compact Source Iodide (CSI) lamp has been used to conduct experiments under controlled conditions. The outdoor test was conducted under the meteorological conditions of Singapore. The component of interest, which produces electricity, will be delivered to PV cells and, hence, there will no heating effect and performance degradation. A layer of water of about 15 mm can eliminate the components of the radiation not contributing to electricity generation. Also, absorbed radiation at the water filter enables to provide hot water.